CompTIA® network+ guide to networks - West, Jill; Dean, Tamara; Andrews, Jean 1946- (Networking (Course Technology, Inc.), 2016)
Master the technical skills and industry know-how to begin an exciting career installing, configuring, and troubleshooting computer networks with the completely updated NETWORK+ GUIDE TO NETWORKS, 7E. You can prepare for success on CompTIA's Network+ N10-006 certification exam with fully mapped coverage of all objectives, including protocols, topologies, hardware, network design, and troubleshooting